Chieftain - Griffin, Rob (The Crowood Press, 2001)
Chieftain was the British Army's first true main battle tank. Designed in the mid 1950's, it became the mainstay of the Tank Corps until its own replacement in the 1980's. This book offers the full design and development history, and covers all of the Chieftain's variants and its second-line use.